2020
DOI: 10.1037/xhp0000748
|View full text |Cite
|
Sign up to set email alerts
|

Is working memory inherently more “precise” than long-term memory? Extremely high fidelity visual long-term memories for frequently encountered objects.

Abstract: 33Long-term memory is often considered easily corruptible, imprecise and inaccurate, especially in 34 comparison to working memory. However, most research used to support these findings relies on 35 weak long-term memories: those where people have had only one brief exposure to an item. Here 36 we investigated the fidelity of visual long-term memory in more naturalistic setting, with 37 repeated exposures, and ask how it compares to visual working memory fidelity. Using 38 psychophysical methods designed to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Experiment 2 showed that repetitions improved delayed recall, substantially increasing the probability of continuous information storage and its precision. These results corroborate the findings of Miner et al (2020), indicating that representations in long-term memory can also have high fidelity provided that multiple traces of the object have been stored.…”
Section: Implication Of Verbal Labeling For Continuous and Categorica...supporting
confidence: 87%
See 4 more Smart Citations
“…Experiment 2 showed that repetitions improved delayed recall, substantially increasing the probability of continuous information storage and its precision. These results corroborate the findings of Miner et al (2020), indicating that representations in long-term memory can also have high fidelity provided that multiple traces of the object have been stored.…”
Section: Implication Of Verbal Labeling For Continuous and Categorica...supporting
confidence: 87%
“…Furthermore, performance in the second presentation of the colored object in the labeling condition would imply four retrievals (two in the first trial + two in the second trial), and hence it should have been even better than performance in the third repetition in the suppression condition. Experiment 2 showed, however, that performance improved linearly with the number of repetitions in visual working memory irrespective of labeling (see also Miner et al, 2020). This is inconsistent with the possibility that labeling benefits visual working memory through retrieval practice.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations